HUBUNGAN PENERIMAAN ORANGTUA DENGAN PRESTASI BELAJAR PADA SISWA SMP NEGERI 2 JOMBANG - , ALVIANNUR HALIM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The development of the child's good character is an essential requirement for survival. In this case, the parents have an important role in educating and teaching their children. So that, the relationship between parent and children must be well established, as well as parental acceptance. According to Rohner in Parental Acceptance-Rejection Theory (Rohner, 1986) stated that emotional warmth and relationship of the parents is an essential requirement for the psychological development of children. Impaired psychological development could affect cognitive and emotional development of the child, and it would affect child's performance in school that could be seen in their learning achievement. Objective: The objective of this study was to determine the presence/absence of relation between parental acceptance with the learning achievement of children in SMP Negeri 2 Jombang. Methods: This research is a descriptive analytic correlational cross-sectional study and quantitative methods. A total of 243 children taken at random, proportional, and the stratification of each generation in SMP Negeri 2 Jombang. They assess parental acceptance of them and then compared with their learning achievement derived from the report card. The data were processed and analyzed with Spearman technique to determine the relation between parental acceptance with learning achievement in students of SMP Negeri 2 Jombang. Results: from 243 data, 45 data excluded so there were 198 data valid. The analysis showed there is influence between parental acceptance with the learning achievement of students of SMP Negeri 2 Jombang, but it was not significant with p = 0.081 (>0.05) in maternal acceptance and p = 0.064 (>0.05) in paternal acceptance. Conclusion: There is a relation of parental acceptance with learning achievement in students of SMP Negeri 2 Jombang school year 2013/2014, but it was not significant.